Eye-tracking-based analysis of pharmacists' thought processes in the dispensing work: research related to the efficiency in dispensing based on right-brain thinking - Toshikazu Tsuji; Kenichiro Nagata; Masayuki Tanaka; Shigeru Hasebe; Takashi Yukita; Mayako Uchida; Kimitaka Suetsugu; Takeshi Hirota; Ichiro Ieiri (BMC, 2024)
Abstract Background Pharmacists should be aware of their thought processes in dispensing work, including differences in the dispensing complexities owing to different drug positions in the left, center, and right areas. Dispensing errors associated with "same-name drugs (a pair of drugs with the same name but a different ingredient quantity)" are prevalent and often negatively affect patients. In this study, using five pairs of comparative models, the gaze movements of pharmacists in dispensing work were analyzed using an eye-tracking method to elucidate their thought processes. Methods We prepared verification slides and displayed them on a prescription monitor and three drug rack monitors. The dispensing information (drug name, drug usage, location display, and total amount) was displayed on a prescription monitor. A total of 180 drugs including five target drugs were displayed on the three drug rack monitors. Total gaze points in the prescription area, those in the drug rack area, total vertical movements between the two areas, and time required to dispense drugs were measured as the four classifications Gaze 1, Gaze 2, Passage, and Time, respectively. First, we defined the two types of location displays as "numeral combination" and "color/symbol combination." Next, we defined two pairs of models A1-A2 (numerals) and B1-B2 (color/symbol) to compare differences between the left and right areas. Moreover, three pairs of models C1-C2 (left), D1-D2 (center), and E1-E2 (right) were established to compare differences between "numeral combination" and "color/symbol combination." Results Significant differences in the complexities of dispensing work were observed in Gaze 2, Passage, and Time between the models A1-A2 (A1<A2), in Gaze 2 between the models B1-B2 (B1>B2), and in Gaze 2 and Time between the models C1-C2, D1-D2, and E1-E2 (C1>C2, D1>D2, and E1>E2, respectively). Conclusions Using the current dispensing rules, pharmacists are not good at dispensing drugs located in the right area. An effective measure for reducing the dispensing complexity is to introduce visual information in the prescription content; the utilization of the right brain facilitates reducing the complexity in the right dispensing area.